Joyful Learning: Upaya Peningkatan Mutu Sumber Daya Manusia bagi Anak Pekerja Migran Indonesia di Sarawak Malaysia - Bariyah, Nurul; Fariastuti, Fariastuti; Wahyudi, Wahyudi; Sulia Sukmawati, Urai; Hasanah, Hasanah (Jurnal Pengabdian Kepada Masyarakat, 2026)
The migration of Indonesian workers to Sarawak Malaysia has created complex social challenges, one of which is limited access to education for their children. This community engagement program aims to enhance the quality of human resources among Indonesian migrant workers’ children through the implementation of the Joyful Learning approach at the Community Learning Center (CLC) in Sarawak. The activity was conducted collaboratively with Universiti Malaysia Sarawak (UNIMAS) and the Consulate General of the Republic of Indonesia in Kuching. The program employed participatory and contextual learning methods that encourage students to learn through play, storytelling, and cultural interaction. Qualitative methods observation, interviews, and reflective discussions were used to assess changes in motivation and learning outcomes. The results indicate that Joyful Learning effectively increased students’ enthusiasm, self-confidence, and participation in the learning process. Despite limited facilities, the approach successfully created a more engaging and meaningful educational atmosphere, showing its potential to be applied sustainably across other CLCs for Indonesian migrant communities abroad.